Understanding service experience and its impact on brand image inhospitality sector - Tukamushaba, Eddy K.; Manhasa, Parikshat S. (International Journal of Hospitality Management, 2015)
tThis paper provides an understanding of customers’ common expectations and other important factorsthat enhance service experience during guest stay in the three selected four star rated hotels in Jammu,Chandigarh and Delhi, India. A structured questionnaire was used to collect data from hotel managers andindividual customers. Guest’s attitudes, their expected and unexpected feedback in addition to analyzingthe important information that helps in finding out particular areas critical to customer service qualityare explored. Overall the results indicate that expectations of the guests and actual experiences are atdisparity. Viable recommendations to the hotel owners in particular and the hospitality industry overallare made which are likely to improve customer’s memorable experience
Keywords: Service quality; Customer experiences; Brand image Customer; Satisfaction India